Diagnostic Accuracy of Ultrasound in Detection of Bladder Masses Keeping Cystoscopy as Gold Standard - Mina Khel, Sapna Salim; Shah, Ghulam Ghuas; Bilal, Muhammad; Asif, Muhammad; Umer, Ummara Siddique; Abid, Hadia (Biological and Clinical Sciences Research Journal, 2025)
Bladder cancer is one of the most common urological malignancies worldwide, with painless hematuria being the predominant presenting symptom. Cystoscopy is considered the gold standard for diagnosis, but it is invasive, costly, and not always feasible in resource-limited settings. Ultrasound, being noninvasive and widely available, is frequently used as an initial imaging modality. Objective: To evaluate the diagnostic accuracy of ultrasound in detecting urinary bladder masses, using cystoscopy and histopathology as the reference standards. Methods: This prospective cross-sectional diagnostic accuracy study was conducted in the Departments of Radiology and Urology, Rehman Medical Institute, Peshawar, from September 2024 to March 2025. Ninety-three patients aged ≥18 years presenting with painless hematuria or dysuria were included. All underwent gray-scale ultrasound of the kidneys, ureters, and bladder, followed by cystoscopy and, where applicable, transurethral resection of bladder tumor (TURBT) with histopathology. Diagnostic accuracy parameters of ultrasound were calculated against cystoscopy/histopathology. Results: The mean age of participants was 69.6 years, with 81 males (87.1%) and 12 females (12.9%). Ultrasound detected bladder masses in 29 patients. Cystoscopy confirmed masses in 32 cases. Ultrasound demonstrated a sensitivity of 87.9%, specificity of 98.3%, positive predictive value of 96.7%, and negative predictive value of 93.7%. Conclusion: Ultrasound is a valuable, noninvasive, and cost-effective modality for the initial evaluation of patients with suspected urinary bladder masses. Although it cannot replace cystoscopy, its high sensitivity and specificity support its role as a first-line investigation, particularly in resource-limited settings.